Pengaruh Whistleblowing System terhadap Fraud Prevention pada Perusahaan Sektor Keuangan Listing di BEI Periode 2022-2024 - Muhammad Rizki Ananda; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2026)
Fraud is a major risk for the financial sector because it can create substantial financial losses and weaken public confidence. This research analyzes the role of the whistleblowing system in preventing fraud, while using firm size as a control variable. The study focuses on financial sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. A quantitative method was applied using secondary data from 195 firm-year observations, and the data were tested through panel data regression with robust standard errors. The findings show that the whistleblowing system has a significant positive influence on fraud prevention. In contrast, firm size does not show a significant effect. Overall, the research model is statistically significant and explains 28.9% of the variation in fraud prevention. These results suggest that an effective whistleblowing system can support stronger corporate governance and help companies reduce the risk of fraud.